PENGEMBANGAN MODUL IPA BERBASIS DISCOVERY LEARNING DALAM MENINGKATKAN, KETRAMPILAN PROSES, PESERTA DIDIK PADA MATERI GETARAN, GELOMBANG, DAN BUNYI - RAHAYU, PUJI; RUMAHORBO, BASA T; WAHYUDI, IRFAN (Jurnal Ilmu Pendidikan Indonesia, 2020)
This research is a research and development that aims to know to create an integrated IPA module, the feasibility of integrated IPA module, the improvement of the activity, science process skill, and student’s learning result by using integrated IPA module, the advantage and disadvantages using integrated IPA module based on discovery learning on vibration, waves, and sounds materials. The research method is research and development. This research conducted in class VIII C of SMP YPK 2 Manokwari with 30 students. The result shows that : 1) The feasibility of integrated IPA module based on discovery learning on vibration, waves, and sounds materials from validator 91,49% with very decent category, IPA teachers got 90,83% with very good category, and the result of try out in small scale got 87,75% 2) The integrated IPA module based on discovery learning on vibration, waves, and sounds can improved the science process skills with skilled categories (63,15%) 3)